Forecasting methods for safeguarding ASEAN-5 stock exchanges during extreme volatility - Chaiboonsri C. (2017)
Copyright © 2017 Inderscience Enterprises Ltd. The main reason for using Bayesian approach and Pickands's dependent function for prediction and estimation in this research is the beginning of the multiplex econometric methods. The multiplex econometric examination resulted that predictive value of the minimum index points on real-time for five stock markets consisting of SGX, KLSE, SET, IDX, and PSE. Comparison of the previous examples should illustrate the wide range of gain or loss values related resulting from changing factors on the economic stimulus policy before the potential occurrence of financial crisis after 2015. As indicated previously, the majority results are only as good as the input data from the selected period, 1987-2015. The results of this research may use to be a signal to present the financial disorder in five ASEAN Exchange markets involving an economic weakening. Moreover, it would be used to guide the defining of any policy for protection of financial disorders.